Political Marketing Strategy of Kustini Sri Purnomo and Danang Maharsa for the 2020 Sleman Regency Election - Dika Pratama; Dian Eka Rahmawati (Universitas Muhammadiyah Yogyakarta, 2023)
This research discusses the capital and political marketing strategy of the regent and deputy regent candidate pairs in the 2020 Sleman District Election. This research identified the political marketing strategy for the victory of the Kustini-Danang pair in the 2020 Sleman Regional Election. This study aims to analyze the capital and strategies used to win elections. The theory used study combined Pierre Bourdieu’s theory of capital and Firmanzah’s theory of Political Marketing 4P (Product, Promotion Price, and Place). This research is qualitative. The data analysis used Qualitative Data Analysis Software (Q-DAS); the tool used was Nvivo 12Plus. The data were obtained from interviews, social media, local media, and other sources of literature, such as documents obtained from the internet, as well as from books, journals, reports and archives related to this research. The results showed that the most significant indicator for the victory of the Kustini-Danang pair is “Price”. This study concludes that the price indicator is the most dominant in winning the regional elections because of image value. The image built by the Kustini-Danang pair is quite strong because Kustini is the wife of the former Sleman regent who served for two terms, and Danang is a DPRD member from the PDIP party so he was able to convince the people of Sleman to vote for the Kustini-Danang pair.